AKUNTABILITAS DAN EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA - Sari, Firda; Diana, Fina; S, Suhendra (Universitas Patria Artha, 2022)
This study aims: (1) to analyze accountability for the management of village fund allocations (ADD) in Maccini Baji Village (2) to analyze the effectiveness of village fund allocation management (ADD) in Maccini Baji Village. Data collection methods used in this research are literature study, interviews and documentation. Furthermore, the research results were analyzed through descriptive-qualitative methods. The data used in this study are primary data and secondary data with the research subjects consisting of the Village Head, Village Secretary, Head of Affairs/staff, and the Maccini Baji Village Community who have an understanding of the management of village fund allocations. The results of this study show that in the implementation of accountability for managing village fund allocations in Maccini Baji village, which is measured using indicators, it is in accordance with Minister of Home Affairs Regulation Number 20 of 2018. Meanwhile, the analysis of the effectiveness of the management of Maccini Baji village fund allocation which is measured using the effectiveness ratio in 2019 and 2020 are in the effective category. This is evident from the success of the Village Government as well as community participation in managing the Village Fund Allocation income, and being able to maximize the needs of the community so that it is felt well by the village community.